Building a Resilience‐Oriented Child Welfare Court System. (March 2017) - Wyman, Robert; Warner‐King, Kelly
Abstract: The child welfare court system wrestles consistently with how to measure success. Preventing child deaths, ensuring child safety, enhancing child well‐being, and faster permanency are some of the metrics used to assess the effectiveness of our system. This article proposes measuring child welfare courts on their principle‐driven expression of values that promote the existence of resilience in families, professionals, and the system itself. It is critical to understand that trauma is not a necessary result of adversity, and the existence of protective factors can make us resilient against the triggering and onset of trauma. Child welfare court systems exist in complexity, and need to be managed for innovation and adaptability. The experience of poverty shared between families and the system is often the curse that weighs against performance, but could be the link that opens expanded capacity. The Court Improvement Training Academy at the University of Washington School of Law provides a framework of values, principles, and examples of work aimed at building resilience‐oriented child welfare court systems.